COMMERCIAL PROPERTY DEVELOPMENT PROGRAM OF HIGHEST AND BEST USE STUDY IN INDUSTRIAL AREA SIER SURABAYA - I. G. Oka Sindhu Pribadi; Meyriana Kesuma; Miya Irawati (Universitas Trisakti, 2022)
Part of Surabaya Industrial Estate Rungkut (SIER) Area is planned to become Central Business District (CBD) in accordance with the direction of the Surabaya City Government. The land use is changed due to the decrease of carrying capacity of the infrastructure in the environment around SIER, caused by density increase since Middle East Ring Road (MERR) was opened in 2012. In addition, some of the areas that became CBD areas are part of the PT SIER area (97.4 Ha). Aim: This study was aimed to determine alternative land functions. Methodology and results: Since CBD is generally dominated by commercial properties, this research focuses on commercial property development programs carried out within the scope of the Highest and Best Use (HBU) Study. This research was conducted through location, site, and market analysis, completed with recommendation for property type in SIER location. Conclusion, significance and impact study: Based on macro market analysis, supply of retail, hotel and apartment property is increasing, while supply of office is decreasing. The results of this study are the best and highest value proposals for the development of commercial property functions (apartments, offices, shopping areas, and hotels), so that the investment is not high risk. In addition, the result can be used as a policy orientation for all interested parties, especially PT SIER in the development of CBD in its area, related to the development stage that is adjusted to the interests and market conditions.